Arteriovenous Fistula Stenosis: A Case Report - Seprian Widasmara; Novi Kurnianingsih; Ardian Rizal; Sasmojo Widito (Universitas Brawijaya, 2021)
BackgroundThe arteriovenous fistula (AVF) is the preferred hemodialysis access type because it has better patency rates and fewer complications than other access types. Dialysis vascular access failure is common, is rated as a critical priority by both patients and health professionals, and is associated with excess morbidity, mortality, and healthcare costs.Case IllustrationA 64 years old man with stage V CKD on routine HD was admitted to hospital with difficulty in cannulation during his last hemodialysis. He already had arteriovenous fistula for hemodialysis access in his left arm since 2 years ago. In the last month before admission, he went to surgery to make hemodialysis access via arteriovenous fistula in his right arm, but failed to mature. Vascular ultrasound on dialysis vascular access was ordered. The examination revealed there was stenosis in the juxta-anastomosis site and cephalic venous stenosis in his left arm. He underwent percutaneous angioplasty with POBA in the anastomose arteriovenous fistula and implantation stent in the left cephalic vein.DiscussionDysfunction of hemodialysis access is a major problem for patients undergoing hemodialysis. It is generally due to venous stenosis, which diminishes flow in the hemodialysis access arteriovenous, thereby leading to poor dialysis. Fistulas tend to develop stenosis most commonly either at the juxta-anastomosis site and the outflow vein. Peripheral venous stenosis is the most common cause of arteriovenous fistula dysfunction and may lead to access thrombosis. The first-line treatment of stenosis should be balloon angioplasty. Stent placement in the peripheral vein is generally not recommended except in special circumstances.ConclusionHemodialysis vascular access is the “lifeline” for patients on hemodialysis. Vascular access-related complications can lead to patient morbidity and reduced quality of life. Surgery often cannot be provided as rapidly as a percutaneous approach. Catheter-based interventions are successful in restoring flow in more than 80% of hemodialysis accesses that undergo stenosis and have replaced surgical revision as the treatment of choice for failing or stenosed accesses